Enhancing Export Performance: Do Energizing Team Learning and Opportunity Recognition Matter? - Ardianita Nur Indah Sari; Iwan Hermawan; Inayah Inayah (Research Synergy Foundation, 2023)
The furniture export performance study departs from an awareness decline in Export Performance (EP) and an innovation index below Singapore, Malaysia, Thailand, Vietnam, and the Philippines in 2021. Thus, this paper aims to build an empirically tested model to build EP. The critical concept is the importance of building innovation through learning and utilizing learning to transform current challenges into opportunities to address various challenges. Organizations must get an agile work team by building Energizing Team Learning (ETL). ETL is offered to strengthen Digital Technology (DT), whose use has been strategically attached to the furniture industry to achieve performance and provide various solutions to problems facilitated by Opportunity Recognition (OR). This study's theoretical gap contradicts the DT to EP research results. The direction of this paper is to develop an appropriate strategy to encourage the presence of EP through ETL, which is used to facilitate the presence of OR to create EP. This research involved 194 furniture exporters in Central Java. The analytical method used is Structural Equation Modeling with the AMOS 22 analysis tool. This study uses the perspective of Knowledge-Based View Theory and empirically proves that DT has an insignificant effect on EP, and ETL and OR managed to mediate DT to EP fully. The strategy to optimize EP is to strengthen DT in the organization, build learning agility through ETL, and apply learning contexts in capturing OR so that implementing this strategy provides empirical evidence to be an optimal strategy. Managers need to make practical implications for the contribution of knowledge built up through the talents of people placed in ETL.